Experimenting with austerity urbanism through public asset management. The case of Grenoble and Bologna - Federica Gatta; Maria Grazia Montesano (Métropoles, 2025)
This paper examines how austerity measures can lead to experimentation in urban policy-making. The concept of austerity has been applied extensively since the 2008 global financial crisis and the subsequent emergence of debt reduction policies. The effects of these policies in different local contexts reveal the existence of a form of austerity urbanism, involving experimentation, especially with regard to public asset management. These experiments combine the production of new urban services, the regeneration of public buildings and land, and the optimisation of public spending, which is paramount. In certain situations, the experimental policies adopt a participatory approach to public resource management. This paper starts with a critical examination of the existing literature on austerity urbanism and posits that there is a link between austerity measures and experimentation. Subsequently, the paper discusses the emergence of particular experiments in public asset management in France and Italy. Lastly, the role of urban trajectories in activating these forms of experimentation is discussed in relation to the preliminary field results from research conducted in Grenoble and Bologna.